The Role of Product Knowledge and Attitudes toward Purchasing Intentions: The Moderating Effect of Religiosity on Halal Cosmetics - Sriminarti, N; Nora, L (KnE Social Sciences, 2018)
This study aimed to explore the influence of the product knowledge, attitude on consumer, purchase intention and the moderating effect of religiosity on halal cosmetics. The samples of this research paper were halal cosmetics consumers. The research used purposive sampling. There were 96 respondents participating in this research. Data were analyzed by using SEM with Warp PLS 4.0. The result indicated that product knowledge and attitude had significant and positive value on the purchase intention. This study proved religiosity as the influence moderation of product knowledge towards purchase intention. However, it cannot be the influence moderation of the attitude towards the purchase intention. The Implication of this study showed that Muslim became smarter and selective on choosing the products to be consumed. Thus, one’s religiosity determined the shaping of consumer intentionbehavior. The high level of religiosity of people would make them to be more selective on using a product. On the other hand, the low level of religiosity of people would make them to be ignorant with the information of halal product. Keywords: Product Knowledge; Attitude; Purchase Intention; Religiosity; Halal Cosmetic, JEL Code:M31